Analysis of the USDA’s 2017 Cow-Calf Management Practices Results: Part 1—Calf Crop and Calving Distribution - Angela Maria Gonella-Diaza; Oscar Alejandro Ojeda; João Bittar; Mario Binelli (EDIS, 2021)
This publication analyzes the calf-crop and calving distribution data reported on NAHMS Beef 1997 and provides insights and practical recommendations. Written by Angela Gonella, Oscar Alejandro Ojeda-Rojas, João Bittar, and Mario Binelli, and published by the UF/IFAS Department of Animal Sciences, November 2021.